Pathways to reduced emergency department and urgent care center use: Lessons from the comprehensive primary care initiative. (30th November 2020) - Timmins, Lori; Peikes, Deborah; McCall, Nancy
Abstract: Objective: To determine the association between a large‐scale, multi‐payer primary care redesign—the Comprehensive Primary Care (CPC) Initiative—on outpatient emergency department (ED) and urgent care center (UCC) use and to identify the types of visits that drive the overall trends observed. Data Sources: Medicare claims data capturing characteristics and outcomes of 565 674 Medicare fee‐for‐service (FFS) beneficiaries attributed to 497 CPC practices and 1 165 284 beneficiaries attributed to 908 comparison practices. Study Design: We used an adjusted difference‐in‐differences framework to test the association between CPC and beneficiaries' ED and UCC use from October 2012 through December 2016. Regression models controlled for baseline practice and patient characteristics and practice‐level clustering of standard errors. Our key outcomes were all‐cause and primary care substitutable (PC substitutable) outpatient ED and UCC visits, and potentially primary care preventable (PPC preventable) ED visits, categorized by the New York University Emergency Department Algorithm. We used a propensity score‐matched comparison group of practices that were similar to CPC practices before CPC on multiple dimensions. Both groups of practices had similar growth in ED and UCC visits in the two‐year period before CPC. Principal Findings: Comprehensive Primary Care practices had 2% ( P = .06) lower growth in all‐cause ED visits than comparison practices. They had 3% ( P = .02) lower growth in PC substitutable ED visits, driven by lower growth in weekday PC substitutable visits (4%, P = .002). There was 3% ( P = .04) lower growth in PPC preventable ED visits with no weekday/nonweekday differential. As expected, our falsification test showed no difference in ED visits for injuries. UCC visits had 9% lower growth for both all‐cause ( P = .08) and PC substitutable visits ( P = .07). Conclusions: Our results suggest that greater access to the practice and more effective primary care both contributed to the lower growth in ED and UCC visits during the initiative.